Historical memory of Ocloro´s river, Barrio Luján, San José, Costa Rica, 1960-2017 - Chaves Villalobos, María del Carmen (2022)
Barrio Luján is a neighborhood located south of Costa Rica's capital, being part of the Cathedral district since 1868, in this neighborhood the working class found a home, which despite the increasing urban development of recent decades, it preserves the characteristics of a working-class neighborhood, with traditional activities passed down from generation to generation. Furthermore, it has been characterized by its communal organization on two main fronts: the community development and the flood management events caused by the Ocloro River. This river has changed over time, not only as a result of the pollution load of solid and liquid waste that it now receives, but also as a result of piping work done in some sections of the river bed, to try to control flooding. This document aims to describe the dynamic process that Barrio Luján has gone through, in order to facilitate understanding of the current situation of the Ocloro´s river and its impact on the environment and the community.